2019
DOI: 10.3389/fimmu.2018.03119
|View full text |Cite
|
Sign up to set email alerts
|

A GMCSF-Neuroantigen Tolerogenic Vaccine Elicits Systemic Lymphocytosis of CD4+ CD25high FOXP3+ Regulatory T Cells in Myelin-Specific TCR Transgenic Mice Contingent Upon Low-Efficiency T Cell Antigen Receptor Recognition

Abstract: Previous studies showed that single-chain fusion proteins comprised of GM-CSF and major encephalitogenic peptides of myelin, when injected subcutaneously in saline, were potent tolerogenic vaccines that suppressed experimental autoimmune encephalomyelitis (EAE) in rats and mice. These tolerogenic vaccines exhibited dominant suppressive activity in inflammatory environments even when emulsified in Complete Freund's Adjuvant (CFA). The current study provides evidence that the mechanism of tolerance was dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 90 publications
2
26
0
Order By: Relevance
“…According to the above considerations and studies on Treg cell activation by APCs, 55 one can speculate that surface expression of specific cytokines or growth factors on EVs can not only drive cellular trafficking and targeting of the latter, but also greatly support their tolerogenic function (Figure 1). In addition, our research findings showed that orally administered EVs may also efficiently suppress an ongoing immune response, as discussed below.…”
Section: Antigen‐specific Tolerance In Autoimmune Responsesmentioning
confidence: 97%
See 2 more Smart Citations
“…According to the above considerations and studies on Treg cell activation by APCs, 55 one can speculate that surface expression of specific cytokines or growth factors on EVs can not only drive cellular trafficking and targeting of the latter, but also greatly support their tolerogenic function (Figure 1). In addition, our research findings showed that orally administered EVs may also efficiently suppress an ongoing immune response, as discussed below.…”
Section: Antigen‐specific Tolerance In Autoimmune Responsesmentioning
confidence: 97%
“…As a consequence, induced Treg cells ameliorated EAE. GM‐CSF binding to the corresponding receptors on myeloid APCs was reported to trigger selective cellular targeting and further promote tolerogenic presentation of MOG peptides to induce the generation of Treg lymphocytes instead of effector T cells 55 …”
Section: Antigen‐specific Tolerance In Autoimmune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified protein was activated by 10 min of exposure to 70 • C, and each prep was verified for bioactivity by induction of FOXP3 in MOG-stimulated 2D2-FIG splenocyte (SPL) cultures. Generation, expression, purification, and bioassay of GMCSF-MOG was performed as described in previous studies (16,19,20). This FP was comprised of the murine GM-CSF cytokine as the N-terminal domain, the peptide sequence comprising MOG35-55, and an eight-histidine C-terminus.…”
Section: Synthetic Peptides Tgf-β Gmcsf-mog and Il-2mentioning
confidence: 99%
“…optimized by incorporating self-antigens that are recognized with intermediate TCR recognition efficiencies (14)(15)(16)(17)(18)(19)(20)(21). Conversely, vaccines incorporating antigens that are recognized with high TCR recognition efficiencies are optimal for induction of immunogenic Tcon responses (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%